Investigating the Level of Awareness of Indian Executives about ESG and the ESG Reporting Software - M V Sunil, Mousumi Sengupta, M. Pradeep, (European Economic Letters (EEL), 2024)
The paper investigated the awareness among Indian executives about the importance of the metrics of the three pillars of ESG and investigated the opinion of the respondents on the features and characteristics of the ESG software. The data revealed that the respondents were aware of the concept of ESG and the present ESG reporting system at their organizations. The category map reveals that Easy use, One-Stop Solutions, Integration with existing software, and, Training and supportive Manual are the features/characteristics of ESG Software, that fall under the “Core quadrant” of the Category map.